A Study on Determining the Parameters of the Ural - 375 Truck under Accelerated Motion - Tran , Tuấn Dũng; Le, Thị Lý (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
For a long time, Ural trucks have been familiar to us in both academic settings and everyday life. However, during operation under varying conditions and terrains, it is still necessary to perform calculations and general evaluations of the vehicle’s parameters to ensure optimal performance and engine longevity. This paper presents the theoretical basis for constructing differential equations and a simulation system in LabVIEW to determine key parameters of the Ural truck during acceleration, such as acceleration rate, traction force, and more. Based on the obtained research and simulation results, it becomes possible to evaluate the operational limits of the Ural truck during acceleration. From this, recommendations for drivers can be made to ensure safe and efficient vehicle operation in real traffic conditions.